ALTERNATIVE TREATMENT OF PATIENTS WITH DIABETIC NEPHROPATHY USING TYPE 2 SODIUM-GLUCOSE COTRANSPORTER INHIBITORS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article presents the results of the research on the alternative treatment of 103 patients with chronic kidney disease developed on the basis of diabetic nephropathy with the use of sodium-glucose cotransporter type 2 inhibitors by improving kidney damage markers and kidney function. Also, comparing the obtained results with the results of other authors' researches, the nephroprotective effect of the drug is once again based in detail.